PENGARUH KEPEMIMPINAN DAN PELATIHAN KERJA TERHADAP DISIPLIN DAN KINERJA (STIE Cendekia Karya Utama, 2021)
This study discusses the influence of leadership and job training on the discipline and performance of the state's crew at the Tanjung Perak Beach and Sea Guard Base, Surabaya. This study uses an explanatory research design with a causal comparative approach. The population in this study were the crew of the ships at the Tanjung Perak Beach and Sea Guard Surabaya, totaling 55 people. The sampling technique used a census. The sample in this study amounted to 55 people. The method of analysis of this research uses path analysis based on multiple linear regressions. The results of this study indicate that leadership directly has a significant effect on the work discipline of ship crew, job training directly has a significant effect on the work discipline of ship crew, leadership directly has a significant effect on the performance of crew members, job training directly has a significant effect on children's performance. ship crew, work discipline directly has a significant effect on the performance of crew members, leadership indirectly has a significant effect on performance through ship crew work discipline, job training indirectly has a significant effect on performance through ship crew work discipline.